Factors associated with iron and folic acid supplementation among pregnant women aged 15-45 years attending Naroosura health centre, Narok County, Kenya - Kotonto, Asenath S.; Wakoli, Albert B. (International Journal Of Community Medicine And Public Health, 2021)
Background: Iron and folic acid are very important nutrients to mothers during pregnancy. Their deficiencies are risk factors for anaemia, preterm delivery and low birth weight. This study aimed to investigate the supplementation of iron and folic acid and the associated factors among pregnant women attending Naroosura health centre, Narok County, Kenya. Methods: This study employed a descriptive cross-sectional study design. Data collection took a period of one month where a total of 123 mothers participated. A self-administered semi-structured questionnaire was used for data collection. Chi-square test was conducted to find associations at a significance level of 0.05. Results: Of the study participants, nearly a third (31.7%) took iron and folic acid supplements daily, over a half (57.7%) indicated that taking iron and folic acid supplements was important to them, about a quarter (24.4%) reported that use of iron and folic acid supplements reduces birth defects and about a third (32%) consumed foods rich in iron and folic acid. Supplementation of iron and folic acid was significantly associated with residence (ꭓ2=4.311, df=1, p=0.038), monthly household income (ꭓ2=10.870, df=4, p=0.028), reduced birth defects (χ2=6.131, df=1, p=0.013) and consumption of iron and folic acid rich foods (χ2=4.163, df=1, p=0.041). Conclusions: The intake as well as supplementation of iron and folic acid is still low. Therefore, both the intake and supplementation of iron and folic acid need to be scaled up.